Proceedings of the 15th International Conference on Ground Penetrating Radar 2014
DOI: 10.1109/icgpr.2014.6970451
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of soil contamination by iron pipe corrosion and its influence on GPR detection

Abstract: It has been observed that the corrosion of iron pipes in soil can produce variations in ground conductivity around the pipe, and that the visibility of such pipes to GPR can be greatly reduced. This new investigation and measurement of the permittivity and conductivity of soil contaminated by iron pipe corrosion products produces more accurate knowledge of permittivity and conductivity data and their likely spatial vari ation with distance from the corroding pipe. The experimental data are the result of monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Some of the results from this research, in terms of the likely electrical properties of the soil surrounding a corroded cast iron pipe, contributed to research aimed at helping understand the frequencies required for GPR to maximise the chances of detecting such pipes, and this work was reported in Pennock et al (2014). The study by Pennock et al (2014) revealed that the frequency of the GPR antenna is an influential factor in detecting corroded iron pipes when using the GPR method. The results of a series of numerical analyses showed that a corroded iron pipe buried in clay soil would be still detectable at frequencies less than or equal to 100…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Some of the results from this research, in terms of the likely electrical properties of the soil surrounding a corroded cast iron pipe, contributed to research aimed at helping understand the frequencies required for GPR to maximise the chances of detecting such pipes, and this work was reported in Pennock et al (2014). The study by Pennock et al (2014) revealed that the frequency of the GPR antenna is an influential factor in detecting corroded iron pipes when using the GPR method. The results of a series of numerical analyses showed that a corroded iron pipe buried in clay soil would be still detectable at frequencies less than or equal to 100…”
Section: Discussionmentioning
confidence: 85%
“…There are a number of factors which can limit or eliminate the use of GPR by attenuating its signal reflection, including: the presence of the clayey soil (Rogers et al, 2008), iron oxide produced by a corroded buried cast iron pipe (Van Dam and Schlager, 2000;Pennock et al, 2014), dissolved metallic ions (Deceuster and Kaufmann, 2005), depth of the water table (Bano, 2006). Pennock et al (2010) examined the reduction in GPR reflection that could occur with corroded materials, based on altered soil permittivity and conductivity initiated by corrosion processes and/or products.…”
Section: Gpr Application For Iron Pipe Condition Assessmentmentioning
confidence: 99%
“…Soil contamination is a serious contamination [26,27] as soil is considered as one of the major sources of life [28]. Compared with other approaches of bioremediation, microbial and environmental researches are more inclined in applying metagenomic approaches to bioremediation [10,29,30].…”
Section: Metagenomic Bioremediation Of Soil Contaminationsmentioning
confidence: 99%